Are There Variations in Personality Traits Between Men and Women? The Evidence is from Indonesian Residents - Riana, Fitria Dina; Toiba, Hery; Rahman, Moh. Shadiqur (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
Non-cognitive skills, such as personality traits, play a vital role in various facets of human life due to their association with individual decision-making. However, personality traits can vary significantly among individuals globally, particularly between males and females. Hence, the primary objective of this study is to analyze the disparities in personality traits between men and women and to investigate how non-cognitive skills influence well-being. The study utilizes nationally representative data from Indonesia, encompassing 17,560 men and 18,825 women. Employing distinct mean t-tests and linear regression estimations, we observe that men tend to exhibit higher levels of openness, conscientiousness, and agreeableness in their personalities compared to women. Conversely, women demonstrate a propensity for higher level of extraversion and neuroticism. Moreover, our analysis reveals that male well-being is positively correlated with extraversion, while female well-being is linked to openness and extraversion traits. These findings underscore the significance of considering personality attributes in crafting economic development policies. Presently, policymakers in emerging nations like Indonesia heavily prioritize cognitive skills such as technical training and technological innovation. This study suggests that incorporating residents' non-cognitive talents into policy-making could potentially lead to enhanced achievements and progress.